Carbon Ion Induces Cell Death and G2/M Arrest Through pRb/E2F1Chk2/Cdc2 Signaling Pathway in X-ray Resistant B16F10 Melanoma Cells - Sha Li; Hefa Huang; Mengjie Xing; Jin Qin; Hong Zhang; Yang Liu; Liping Zhang; Chao Zhang; Zhongze Tian; Xingxin Gao; Rui Zhao; Aihong Mao (SAGE Publishing, 2022)
To explore the effect of high-LET carbon ion (C-ion) radiation on malignant melanoma, we systematically compared the radiobiological effects of C-ion with that of X-rays in B16F10 melanoma cells. Results showed that C-ion radiation statistically inhibited clonogenic survival capacity of B16F10 melanoma cells. The RBE was 3.7 at D 10 levels, meaning 1.0 Gy C-ion should cause the same biological effect as ≥ 3.0 Gy X-rays. In addition, we also observed a stronger proliferation-inhibiting and higher ratio of cell apoptosis and necrosis in B16F10 cells treated with C-ion than X-rays. Moreover, C-ion radiation exhibited stronger and long-lasting G2/M arrest than X-rays. As an underlying mechanism, we speculated that C-ion radiation-induced G2/M block through activating pRb/E2F1/Chk2 pathway. With these results, we highlighted the potential of C-ion in treatment of cutaneous melanoma. Further, in vitro experiments as well as clinical trials are needed to further evaluate the effect of carbon ion radiotherapy in melanoma.